«Cosmic philosophy» of A. L. Chizhevsky: essence and its place in system of Russian cosmism - Karako, Petr S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article investigates the content of poetry, natural-scientific and philosophical views of the prominent representative of Russian cosmism A. L. Chizhevsky about the dependence of the existence of all living of biosphere of the Earth from the Sun and other cosmic factors. The article emphasizes the contribution of this reperesentiative of Russian cosmism to the substantiation of the integrity of Russian cosmism, its humanistic expression and significance for solving the actual problems of our time. Moreover, the article reveals the controversial ideas, concerning the interpretation of the determination of the world-historical process.
Keywords: nature; biosphere; heliobiology; heliolater; cosmism; cosmic lyric poetry; cosmic philosophy; solar activity; world-historical process